Tests of the FONT3 linear collider intra-train beam feedback system at the ATF - Burrows, P; Christian, G; Clarke, C; Khah, H; Hartin, T; Molloy, S; White, G; Kalinin, A; Perry, C; Frisch, J; Markiewicz, T; McCormick, D; et al. (2005)
We report preliminary results of beam tests of the FONT3 Linear Collider intra-train position feedback system prototype at the Accelerator Test Facility at KEK. The feedback system incorporates a novel beam position monitor (BPM) processor with a latency below 5 nanoseconds, and a kicker driver amplifier with similar low latency. The 56 nanosecond-long bunchtrain in the ATF extraction line was used to test the prototype BPM processor. The achieved latency will allow a demonstration of intra-train feedback on timescales relevant even for the CLIC Linear Collider design. © 2005 IEEE.